Determinants of Farmers’ Agricultural Diversification: The Case of Cambodia - Seng, Kimty (Asian Journal of Agriculture and Rural Development, 2014)
A Heckman sample selection approach is employed with the data on Cambodia Socio-Economic Survey CSES-2007 to explore price and non-price factors determining farmers’ crop diversification decision, and consequently affecting diversification intensity. The findings suggest that high relative price discourages farmers from diversifying crops. Irrigation, agricultural equipment ownership and farming expenditure have significantly positive effects on the decision, and sequentially increasing the intensity. Arable land size per household member, agricultural and transportation equipments have positive correlation with the diversification decision. Small scale of farming is a major hindrance to the decision, and consequently reducing the intensity. Land dispute, one of the main institutional matters in Cambodia, is found to have significantly negative marginal-effect on farmers’ decision on crop diversification.